Ensino de enfermagem em centro cirúrgico e central de material e esterilização: avaliação das matrizes curriculares dos cursos de graduação no estado do Pará - COSTA, Pedro Paulo da Silva (2020)
Introduction: curricular transformations have changed the models of attention of the teaching of individuals to collectivity, and with this the programmatic programs, such as those of the Surgical and Central Center of Material and Sterilization, the tests are reduced and / or abstracted of the undergraduate curricula in nursing. Currently, there is no context of the CC and the CME, the nurses who perform basic care and scientific assistance activities, for example, as the main technical managers of the basic units. Objective: To analyze how Nursing disciplines in the Material and Sterilization Center and Surgical Center in the curricular structures of undergraduate nursing courses in Pará. Method: Descriptive study with quantitative approach, in the curriculum matrices of undergraduate nursing courses, from the disciplines of the Surgical Center and Central Material and Sterilization, whose data were collected on the websites of the institutions that used the registration in the e-MEC platform, through an instrument designed for this study, with information related to the institution, subjects offered in the area, location of the subject (s) in the curriculum and workload. The captured data were released in Excel 2016 to perform descriptive statistics. Results: Of the 23 courses analyzed, two cities in Pará concentrate 62.97% of the vacancies from all over the state of Pará, 78% are offered by private institutions, with an average of 11.28 hours in private institutions and 88.8 hours in public ones. In which, 56.42% of the HEIs presented a preferential logic of workload distribution for subjects between 60 to 120 hours in CC and CME subjects. Final considerations: There was a predominance of private institutions that offer undergraduate nursing and there are courses that do not offer specialized discipline in Perioperative Nursing. It was also evidenced that there was no standardization of nomenclature and period for offering this discipline. Concomitantly suggest the encouragement for further research in the area on how the theoretical and practical contents of this discipline are taught.